2022
DOI: 10.3168/jds.2021-21567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium-chain fatty acids on growth, health, and immune response of dairy calves

Abstract: It is necessary for the dairy industry to reduce calf morbidity and mortality, and the reliance on antibiotics to treat sick calves, to address the growing concern regarding antibiotic resistant bacteria. The primary objective of this study was to evaluate the effect that feeding dairy calves medium-chain fatty acids (MCFA) has on growth performance and health, and the secondary objective was to evaluate the effect of MCFA on energy status around weaning and the adaptive immune response following a vaccine cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The correlation between the concentrations of blood GLU, BHBA, and NEFA and the energy status of calves had been reported [ 44 ]. In the present study, the serum concentration of GLU in the PLO group decreased compared with the CCO and CON groups, which might be explained by the starter intake that tended to be lower in the PLO group than in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the concentrations of blood GLU, BHBA, and NEFA and the energy status of calves had been reported [ 44 ]. In the present study, the serum concentration of GLU in the PLO group decreased compared with the CCO and CON groups, which might be explained by the starter intake that tended to be lower in the PLO group than in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that feeding octanoate to cachectic patients increased concentrations of acylated ghrelin in plasma [ 18 ]. Octanoate is easily absorbed [ 19 ] and used as a supplementary energy source to improve performance in calves [ 20 , 21 ]. Furthermore, calcium salts of fatty acids bypass the rumen without fermentation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%